The ketogenic diet: Pros and cons - O'Neill, Blair; Raggi, Paolo (Atherosclerosis, 2020)
Diets have been at the center of animated debates for decades and many claims have been made in one direction or the other by supporters of opposite camps, often with limited evidence. At times emphasis has been put on a single new aspect that the previous diets had overlooked and the new one was to embrace in order to improve weight loss and well-being. Unfortunately, very few randomized clinical trials involving diets have addressed the combined question of weight loss and cardiovascular outcomes. The recently introduced ketogenic diet requires a rigorous limitation of carbohydrates while allowing a liberal ingestion of fats (including saturated fats) and has generated a flurry of interest with many taking the pro position and as many taking the cons position. The ketogenic diet causes a rapid and sensible weight loss along with favourable biomarker changes, such as a reduction in serum hemoglobin A1c in patients with diabetes mellitus type 2. However, it also causes a substantial rise in low density lipoprotein cholesterol levels and many physicians are therefore hesitant to endorse it. In view of the popular uptake of the keto diet even among subjects not in need of weight loss, there is some preoccupation with the potential long-term consequences of a wide embrace of this diet by large segments of the population. On the contrary, numerous lines of evidence show that plant-based diets are associated with reduction in oncological and cardiovascular diseases and a prolonged life span. The debate reproduced in this article took place during a continuous medical education program between two cardiologists with largely differing views on the matter of effectiveness, sustainability, and safety of the ketogenic diet compared to alternative options. •Most diets are supported by little rigorous scientific evidence.•The ketogenic diet requires a firm restriction of carbohydrates and allows liberal ingestion of fats.•The ketogenic diet induces a rapid weight loss and reduction in hemoglobin A1c, but raises LDL cholesterol.•Other diets are as effective, more sustainable and safer.